Neighborhood story. 3 - Yazawa, Ai, 1967- (Shojo beat manga., 2024)
Welcome to Happy Berry! No, this isn't a fruit stand, but the label dreamed up by aspiring fashion designer Mikako Koda. In her quest to make a name for herself in the fashion world, Mikako enters Yazawa Arts Academy, a prestigious art school, alongside her strictly platonic childhood friend Tsutomu. But there's one problem--Tsutomu's uncanny resemblance to a rock star skyrockets him to popularity and leads him to date the prettiest girl in school. Now Mikako can't help but wonder if what she feels is jealousy. The members of Akindo decide to spend their summer break at Mariko's villa. When Mariko's first love, Shu, unexpectedly appears in the villa next door, Mariko finds herself torn between her past life with him and her present one with Yusuke. In a daring move, Mariko rushes to confront Shu in the midst of a raging typhoon. Yusuke, fueled by jealousy, charges into the storm after her, with Ayumi hot on his heels. Meanwhile, Mikako throws herself into preparations for Yaza Arts Academy's annual school festival. Her relationship with Tsutomu takes a tumultuous turn as he struggles to find a path in life. With sparks flying, their arguments escalate when Tsutomu can't contain his jealousy over Mikako's mom's charming new assistant. As their love teeters on the brink, an extraordinary opportunity arises, forcing Mikako to confront her deepest desires and make a life-altering decision.